A-6G and A-20C Polymorphisms in the Angiotensinogen Promoter and Hypertension Risk in Chinese: A Meta-Analysis - Gu, Wei (Public Library of Science, 2011)
BACKGROUND: Numerous studies in Chinese populations have evaluated the association between the A-6G and A-20C polymorphisms in the promoter region of angiotensinogen gene and hypertension. However, the results remain conflicting. We carried out a meta-analysis for these associations. METHODS AND RESULTS: Case–control studies in Chinese and English publications were identified by searching the MEDLINE, EMBASE, CNKI, Wanfang, CBM, and VIP databases. The random-effects model was applied for dichotomous outcomes to combine the results of the individual studies. We finally selected 24 studies containing 5932 hypertensive patients and 5231 normotensive controls. Overall, we found significant association between the A-6G polymorphism and the decreased risk of hypertension in the dominant genetic model (AA+AG vs. GG: P = 0.001, OR = 0.71, 95%CI 0.57–0.87, P(heterogeneity) = 0.96). The A-20C polymorphism was significantly associated with the increased risk for hypertension in the allele comparison (C vs. A: P = 0.03, OR = 1.14, 95%CI 1.02–1.27, P(heterogeneity) = 0.92) and recessive genetic model (CC vs. CA+AA: P = 0.005, OR = 1.71, 95%CI 1.18–2.48, P(heterogeneity) = 0.99). In the subgroup analysis by ethnicity, significant association was also found among Han Chinese for both A-6G and A-20C polymorphisms. A borderline significantly decreased risk of hypertension between A-6G and Chinese Mongolian was seen in the allele comparison (A vs. G: P = 0.05, OR = 0.79, 95%CI 0.62–1.00, P(heterogeneity) = 0.84). CONCLUSION: Our meta-analysis indicated significant association between angiotensinogen promoter polymorphisms and hypertension in the Chinese populations, especially in Han Chinese.